(untitled) (GEOmedia, 2022)
GEOmedia interviews Gian Bartolomeo Siletto, geologist, official representative for the Spatial Data Infrastructure (IDT) of Regione Piemonte. Conversation with Umberto Trivelloni, Head of the IDT of the Veneto Region, Delio Brentan, P.M. for the IT part of the IDT, and Andrea Semenzato Analyst GIS Engineering Ingegneria Informatica S.p.A